Spesialis media sosial dan promosi kesehatan publik: Studi kasus kampanye vasektomi - Tresnawati, Agustina; Rahadi (Jurnal Mahasiswa Komunikasi Cantrik, 2025)
This study aims to analyze the role of social media specialists in vasectomy campaigns through the Instagram account @kemendukbanggabkkbnjatim. The low participation of men in the Family Planning program due to stigma and limited health literacy underlines the need for an effective digital communication strategy. This study uses a qualitative approach. Data were collected through campaign posts and in-depth interviews with the social media specialist at BKKBN East Java. The results show that the social media specialist plays a role in the pre-production stage (message design and audience analysis), the implementation stage (production and distribution of educational content based on positive narratives), and the evaluation stage (insight analysis for strategic decision-making). The findings of this study emphasize that the success of digital health campaigns is determined not only by metrics such as engagement and reach, but also by the ability of communication actors to perform their roles strategically, creatively, and reflectively, thereby contributing to the development of digital health communication studies based on professional roles.